PERANAN DAN KONTRIBUSI SUB SEKTOR PERKEBUNAN DI PROVINSI JAMBI - Ahmad Soleh (Jurnal Ilmiah Universitas Batanghari Jambi, 2018)
The role of the sub plantation sector in developing the economy of the province of Jambi is no doubt already seen from the large number of residents who work and drape perekonomiannya in sub plantation sector. the data showed more than 60 percent of farmland in the province of Jambi is used as a plantation. The problem related goals of this research are (1) to analyze the development of the vast land, labor, and GRP sub plantation sector in the province of Jambi, (2) analyze contributions subplantation sector against the agricultural sector and GDP the province of Jambi, (3) analyze the effect of Extensive Land and labor against the Output of the Sub Sector Plantation Jambi province. The methods used in this research is descriptive qualitative and quantitative models by using regression Linear Regression and the contribution Multiplied by the method of OLS. The research results showed that (1) the development of land area, the workforce and GDP of sub sectors of the 2000-2015 period of Jambi province plantation continues to increase each year. (2) the variable land area and number of labor jointly or simultaneous affect GDP sub plantation sector province of Jambi. In the partial variable positive effect land area and significantly to GDP sub plantation sector province of Jambi. While labor has no effect significantly to GDP sub plantation sector province of Jambi.Keyword:P DRB, Estates, Labor, Land Area